Self-Confidence And Digital Literacy Mediate: The Effect Of Entrepreneurial Knowledge On The Intention To Start An E-Business (A Study Of Vocational High School Students In Pasuruan) - Yusuf, Yusuf; Cipto Wardoyo; Ludi Wishnu Wardana (International journal of technology and education research, 2025)
This study aims to analyze the effect of entrepreneurial knowledge on the intention to start an e-business among students at SMKN Pasuruan, with digital literacy and self-confidence as mediators. The main issues raised are whether entrepreneurial knowledge directly affects the intention to start a business and what role digital literacy and self-confidence play in this process. The method used is a quantitative approach with data collection through questionnaires from vocational high school students in Pasuruan. The data were analyzed using a path analysis model to test the relationship between the variables studied. This study also adopted a cross-sectional design to see the relationship between variables at a certain point in time. The results show that entrepreneurial knowledge does not have a direct impact on e-business entrepreneurial intention, but it has an indirect effect through self-confidence and digital literacy. In conclusion, increasing self-confidence and digital literacy is very important to encourage entrepreneurial intention, while entrepreneurial knowledge needs to be supported by students' psychological factors and digital capabilities.